PRODUÇÃO DE LIPOSSOMAS DE CREATINA, AVALIAÇÃO DA TOXICIDADE E DE EFEITO NEUROPROTETOR EM MODELO ANIMAL DE NEURODEGENERAÇÃO - Borin, Diego Becker (2017)
The pathophysiology of neurodegenerative diseases is associated with neuronal loss or dysfunction, whose characteristics are determined due to cerebral area affected and progression of the disease. Creatine has physiological importance as energy buffer and storage having protective effects in animal models of neurodegenerative diseases. However, its permeability through the blood-brain barrier (BBB) is very low. The objective of this study is was developing a nanoliposome carrier to facilitate the delivery of creatine to the central nervous system (CNS), thus could potentiate the effects of creatine. In order to test the safety of liposomes toxicity, assays were performed in cell culture and in vivo, as well as analyzed in streptozotocin-induced (STZ) dementia model. The method of production of liposomes by ethanol injection, proved to be efficient, since particles with a polydispersion index (PDI) of 0,237, negative Zeta potential (-12.5 mV) and average size of 213 nm were obtained. The size was confirmed by transmission electron microscopy where spherical particles of 100-200 nm were observed. In in vitro toxicity assays, blank liposomes (without creatine - BL) as well as creatine liposomes (CrL) at concentrations of 0.02 and 0.2 mg/mL did not alter the viability of VERO cells cultured. It also did not alter viability of neural cells in hippocampal slices from adult rats. In toxicity assays in vivo, subchronic treatment with both liposomes did no changes hematological and biochemical markers in blood of young rats, but an increased in creatine concentrations were observed in the brains of CrL-treated animals was observed. In the animal model of STZ-induced dementia in adult mice, behavioral changes such as habituation memory deficit and long-term aversive memory were reversed by 21 days treatment with free creatine and CrL. The animals of the STZ groups did not present alterations in energetic metabolism enzymes in the hippocampus, but they showed a reduction in creatine levels in cerebral tissue, which was reversed by the treatment with free creatine and CrL. It is suggested from the results that CrL can be used safely, but further studies should be performed to verify its performance in other neurodegeneration models.